PROSES BERPIKIR STATISTIS SISWA SEKOLAH DASAR BERGAYA KOGNITIF FIELD INDEPENDENT - Umi Nur Qomariyah; Siti Dinarti (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2021)
The purpose of this research is to describe students’ statistical thinking process which is cognitive field independent (FI) styled in solving statistical problem. This is an explorative research with qualitative descriptive approach. The subjects of this research were VI grade students of SDI Roushon Fikr. This research started from giving competence pre-test and Group Embedded Figure Test (GEFT) to get two research subjects which were cognitive Field Independent (FI) styled. The data collection was carried out through combination of interview and written assignment analysis. The data analysis involved procedures of data reduction, presentation, conclusion and verification. The data was validated by time triangulation. The research result showed that, in general, FI subjects had fulfilled four indicators of statistical thinking, including describing data presentation, organizing and reducing data, presenting, analyzing and interpreting data. The weakness was unable to make complete conclusion from given data.